A reappraisal of Galbraith's challenge to Consumer Sovereignty: preferences, welfare and the non-neutrality thesis*. Issue 2 (3rd March 2020) - Chirat, Alexandre
Abstract: The aim of the paper is to provide an exegesis of Galbraith's theory of consumption and the conception of preferences on which it is grounded, which has often been misunderstood. From the point of view of the history of economic thought, this paper sheds new light on the origins of Galbraith's analysis of consumption. This reappraisal also leads us to show that the latter is bound to a challenge to the Consumer Sovereignty Principle. Consequently, Galbraith's theory contradicts the logic underlying Welfare Economics. Thanks to this exegesis, I finally explain the rationale behind Galbraith's endorsement of the thesis of non-neutrality on the problem of value judgments in economics, which is illustrated by his presidential address to the American Economic Association.